Psychological Interventions for Post-traumatic Stress Symptoms in Psychosis: A Systematic Review of Outcomes - Swan, Sarah; Keen, Nadine; Reynolds, Nicola; Onwumere, Juliana (Frontiers in Psychology, 2017)
Individuals with severe mental health problems, such as psychosis, are consistently shown to have experienced high levels of past traumatic events. They are also at an increased risk of further traumatisation through victimisation events such as crime and assault. The experience of psychosis itself and psychiatric hospitalisation have also been recognised to be sufficiently traumatic to lead to the development of post-traumatic stress (PTS) symptoms. Rates of post-traumatic stress disorder (PTSD) are elevated in people with psychosis compared to the general population. The current guidance for the treatment of PTSD is informed by an evidence base predominately limited to populations without co-morbid psychiatric disorders. The systematic review therefore sought to present the current available literature on the use of psychological treatments targeting PTS symptoms in a population with a primary diagnosis of a psychotic disorder. The review aimed to investigate the effect of these interventions on PTS symptoms and also the effect on secondary domains such as psychotic symptoms, mood, anxiety and functioning. Fifteen studies were identified reporting on cognitive behaviour therapy, prolonged exposure, eye movement desensitisation and reprocessing and written emotional disclosure. The review provides support for the safe use of trauma-focused psychological interventions in groups of people with severe mental health problems. Overall, the interventions were found to be effective in reducing PTS symptoms. Results were mixed with regard to secondary effects on additional domains. Further research including studies employing sufficiently powered methodologically rigorous designs is indicated.